Systematic Literature Review: Web-Based Payroll Information System Software Development Methods - Muhammad Fazly Qusyairy; Imron Rizki Maulana; Salwa Putri Kamilah (Universitas Sains Indonesia Publishing, 2025)
This research aims to conduct a systematic review of software development methods used in creating web-based payroll information systems, focusing on two primary methodologies: Waterfall and Agile. Payroll information systems are a crucial component of human resource management, demanding reliability, security, and easy access via a web platform. Through a Systematic Literature Review (SLR) approach, this study gathered and analyzed various research discussing the application of Waterfall and Agile methods in developing web-based payroll systems. The review's findings indicate that the Waterfall method is frequently employed in projects with stable and clearly defined requirements. In contrast, the Agile method is chosen for its flexibility in quickly accommodating changing user needs. Security aspects, integration with other systems, and efficient data management are key focuses in payroll system development. This research concludes that the choice of development method must align with project characteristics and organizational needs to ensure web-based payroll systems are developed effectively and efficiently. These findings can serve as a reference for developers and researchers in designing optimal payroll information systems.